Judaism and Other Religions - Brill, Alan. author. aut Link
XIV, 275 p.
Keywords: With insight and scholarship, Alan Brill crisply outlines the traditional Jewish approaches to other religions for an age of globalization. He provides a fresh perspective on Biblical and Rabbinic texts, offering new ways of thinking about other faiths. In the majority of volume, he develops the categories of theology of religions for Jewish text and arranges the texts according classification widely used in interfaith work: inclusivist, exclusivist, universalist, and pluralist. Judaism and Other Religions is essential for a Jewish theological understanding of the various issues in encounters with other religions. With passion and clarity, Brill argues that in today's world of strong religious passions and intolerance, it is necessary to go beyond secular tolerance toward moderate and mediating religious positions. .